DESIGN AND ANALYSIS OF A FRONT SUSPENSION COIL SPRING FOR THREE WHEELER VEHICLE - Mr. Harshad B. Pawar; Prof. Amol R. Patil; Dr. Sanjay B. Zope (International Journal of Innovations in Engineering Research and Technology, 2021)
Basically the spring is a flexible component of suspension system. In Modern transport vehicles usually use light coil springs. For this reason present paper used the analytical methods and finite element analysis for the selection of helical compression spring with number of turns. Using Finite Element Analysis completed the modelling, meshing and post processing of front suspension spring. The present work attempts to analyze the load of the three wheeler vehicle front suspension spring with SP ST GRD II material. This investigation includes comparison of software and theoretical analyses of coil spring made of SP ST GRD II material suggested the suitability for optimum design. This work also determined the structural strength of coil spring using the finite element analysis. Based on theoretical and software result comparison the optimum turns which meet all requirements was suggested.